Exploring Junior High School Students' Perception on The Implementation of Picture Series as Media for Learning Writing: A Qualitative Descriptive Study: A Qualitative Descriptive Study - Ayu, Chlorida Metana; Fitriyah, Siti Masrifatul; Hudori, Rizki Febri Andika (English Education Study Program, 2024)
Abstract In this 2.0 education era, many English teachers use various visual aids to help students writing performance. One of the visual instructional media that is used picture series. Picture series is defined as a group of several pictures that describe the atmosphere that is told and show continuity between one picture and another. This research was descriptive qualitative research. This research was conducted at a junior high school in Jember with the 23 students as participants. The researcher used the close-ended, and open-ended questionnaires instrument. Based on the data obtained, the results of this research found that the first research question about students’ perceptions on teaching writing descriptive text using picture series, the researcher found that when the teacher used picture series, students were more enthusiastic to follow the lesson. The previous results indicated that there was an overwhelmingly positive reception to the teacher's teaching method using picture series. The students reported that this enjoyable method made them more eager to learn and more creative in their approach to their studies. Then, the second research question about students’ expectation in this study showed that the students have expressed their satisfaction with the efficiency and effectiveness of their writing teacher in delivering clear and concise material, providing relevant and helpful examples, assigning tasks that are pertinent to what they have learnt, and providing feedback on their work. It is positive to see that the students value their teacher's approach, which has led to their increased motivation and creativity in their learning. Keywords: Learning method, Perception, Picture series, Writing